2021
DOI: 10.3390/en14238024
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Control to Improve the Ramp-Rate of a Gas Turbine: Optimization of Control Schedule

Abstract: As the proportion of power generation using renewable energy increases, it is important to improve the operational flexibility of gas turbines (GTs) for the stability of power grids. Increasing the ramp-rate of GTs is a general solution. However, a higher ramp-rate increases the turbine inlet temperature (TIT), its rate of change, and the fluctuation of the frequency of produced electricity, which are negative side effects. This study proposes a method to optimize the set-point schedule for a PID controller to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 40 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…Such an approach is generally accepted in the minimization of fuel consumption in complex powertrains [26] because it allows the design of a supervisory controller to optimize the power flows in the propulsion system with a small computational effort. However, this approach requires the mission to be known a priori and is not able to handle feedback control problems or to take into account the dynamic response of the energy converters to a variable power request that affects the shaft dynamic in a rotorcraft or the dynamic behavior of the fuel valve [28]. A dynamic model of the whole power system, including the twin rotors, is currently being implemented by some of the authors of this investigation and preliminary results can be found in [29].…”
Section: Proposed Methodology For the Air-taximentioning
confidence: 99%
“…Such an approach is generally accepted in the minimization of fuel consumption in complex powertrains [26] because it allows the design of a supervisory controller to optimize the power flows in the propulsion system with a small computational effort. However, this approach requires the mission to be known a priori and is not able to handle feedback control problems or to take into account the dynamic response of the energy converters to a variable power request that affects the shaft dynamic in a rotorcraft or the dynamic behavior of the fuel valve [28]. A dynamic model of the whole power system, including the twin rotors, is currently being implemented by some of the authors of this investigation and preliminary results can be found in [29].…”
Section: Proposed Methodology For the Air-taximentioning
confidence: 99%
“…Due to the increased use of Gas Turbine Engines (GTEs) in industries such as aerospace and power generation and in power plants, improving their performance is of particular importance for different applications [1][2][3][4][5]. In addition to complex nonlinear systems, these engines should ensure safe and frugal operation during the flight.…”
Section: Introductionmentioning
confidence: 99%